HUBUNGAN MP ASI DINI DENGAN DIARE PADA BAYI 0-6 BULAN DI PUSKESMAS STABAT - Yerni, Arnof (Jurnal Keperawatan Priority, 2020)
Weaning food for breastfeeding babies should always be given at the appropriate time, meaning that all babies should start get weaning food from age six months old and counting. The research was done in Puskesmas Stabat (Stabat Community Health Center), Stabat District, Langkat Regency, from December 2016 to February 2017. Theobjective of this research is to assess the correlation of early weaning food giving and diarrhea incidence in 0 – 6 months babies. This research used a descriptive correlation study design. The population of the research is all mothers with 0 – 6 months old babies in Puskesmas Stabat numbering 389 people. The sample of the research is 40 people, or 10 % of the population, using accidental sampling technique. The independent variable is early weaning food giving to 0 – 6 months old babies, and the dependent variable being diarrhea incidence. The data was collected using questionnaires and interviews, then analyzed using chi squaretest (CI 95% anda= 0,05). The statistical test showed the correlation of early weaning food giving and diarrhea incidence in 0-6 months old babies (p-value= 0,001) as p < 0,05 which means there is a significant correlation between early weaning food with diarrhea incidence. The conclusion of the research is that early weaning food giving influences diarrhea incidence in 0 – 6 months old babies at Puskesmas Stabat.